Examining Relationship between Electricity Consumption and its Major Determinants in Pakistan - Zaman, Mudassir; Shaheen, Farzana; Haider, Azad; Qamar, Sadia (International Journal of Energy Economics and Policy, 2015)
The objective of the study is to examine the relationship between electricity consumption and its major determinants; particularly economic growth, number of electricity customers, electricity prices and electricity shortages in Pakistan using time series data from 1972 to 2012. The study employed the Johansen cointegration test to examine relationship between electricity consumption and its determinants. Multivariate granger causality test is then applied to determine the causality direction between electricity consumption and its major determinants. The results reveal that determinants of electricity consumption function are cointegrated and economic growth, number of electricity customers are positively related to electricity consumption, while electricity price and electricity shortages are negatively related to electricity consumption in Pakistan. However, bidirectional causality found between electricity consumption, economic growth and electricity customers except electricity prices which is exogenous determined. The short run, long run elasticities and multivariate granger causality results implies that at different time frame there is need to implement different policies for Pakistan. There is need to revise electricity pricing policy and find alternative renewable sources to generate low cost electricity and further need to enhance energy management expertise to cope with crises in an efficient way. Keywords: Electricity consumption; Economic growth; Electricity customers; Pakistan JEL Classifications: Q4; Q43